2012
DOI: 10.3109/08039488.2012.655308
|View full text |Cite
|
Sign up to set email alerts
|

The Norwegian version of the PTSD Checklist (PCL): Construct validity in a community sample of 2004 tsunami survivors

Abstract: The Norwegian version of the PCL-S performed well as a diagnostic instrument for detecting PTSD in epidemiological research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 15 publications
1
53
0
Order By: Relevance
“…Twenty-four percent of the sample reported PTSD symptoms that meet the criteria for probable PTSD according to the flowchart method (Hansen, Nissen, & Heir, 2013). In line with the specifications of DSM-IV, this procedure requires one positive score in cluster B, three in cluster C, and two in cluster D (Hem et al, 2012). Furthermore, 22% of the respondents reported a sum of PTSD symptoms over the PCL cut point at 45, and 50% reported a sum of PTSD symptoms over the PCL cut point at 30 (VA National Center for PTSD, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four percent of the sample reported PTSD symptoms that meet the criteria for probable PTSD according to the flowchart method (Hansen, Nissen, & Heir, 2013). In line with the specifications of DSM-IV, this procedure requires one positive score in cluster B, three in cluster C, and two in cluster D (Hem et al, 2012). Furthermore, 22% of the respondents reported a sum of PTSD symptoms over the PCL cut point at 45, and 50% reported a sum of PTSD symptoms over the PCL cut point at 30 (VA National Center for PTSD, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Posttraumatic stress was assessed with the Norwegian version of the PCL-S (Hem, Hussain, Wentzel-Larsen, & Heir, 2012). The PCL-S is a 17-item self-administered questionnaire that assesses PTSD symptom severity (per DSM-IV), and the items were specifically linked to the bomb explosion.…”
Section: Methodsmentioning
confidence: 99%
“…Foreign translations . Several articles using foreign translations of the PCL‐S were located in the literature, accompanied by various diverse psychometric evidence, including two in Norwegian (Blix, Bang Hansen, Skogbrott Birkeland, Nissen, & Heir, ; Hem, Hussain, Wentzel‐Larsen, & Heir, ), two in French (Dubosc et al, ; Ventureyra, Yao, Cottraux, Note, & De Mey‐Guillard, ), and three in Chinese (Erbes, Meis, Polusny, & Compton, ; Jenkins, Belanger, Connally, Boals, & Durón, ; L. Wang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the Norwegian version of PCL has been shown to perform well as a diagnostic instrument for detecting PTSD in epidemiological research 6. Also, we have not considered fulfilment of the DSM A criteria, but only taken into account the number of symptoms in each symptom cluster.…”
Section: Discussionmentioning
confidence: 99%
“…To assess PTSD symptoms, the Norwegian version of the PCL, was applied 6. The PCL was first introduced in 1993 by Weathers et al 7 and it is now one of the most frequently used self-reported measures on PTSD symptoms.…”
Section: Methodsmentioning
confidence: 99%